On the Quantum Electrodynamics of Nanophotonic Systems - Грицунов, А. В.; Бондаренко, И. Н.; Пащенко, А. Г.; Бабиченко, О. Ю.; Одаренко, Е. Н. (My University, 2020)
Problems of quantum electrodynamics of nanoobjects essential for development of new nanophotonic systems are discussed. According to the theory of natural oscillatory systems (NOSs), “interaction” between the objects is interpreted as a quantum-dynamic phenomenon meaning a stable trend arising from the quantum chaos. As an opposite, “interchange” is denominated as the permanent stochastic exchange with action quanta between different NOSs in 4D spacetime, being the physical base of the quantum chaos. The Tetrode-Wheeler-Feynman’s concept of “direct interparticle action” is reconciled with both the quantum radiation-absorption and the Coulomb interaction. A conservation law for the action is supposed to be a necessary condition for the momentum-energy conservation. The “classic” conservation law for the momentum-energy is considered as derivative, being valid for the momentum as well as some physical value that is an integral over 3D space from a linear combination of stress-energy tensor principal diagonal terms. Such redefinition enables the unconditional quantization of the energy unlike “orthodox” quantum theory.
Keywords: nanotechnology; nanophotonic; distributed oscillatory system; matter wave; momentum-energy